Temperature dependent viscosity of mixtures of ionic liquids at different compositions - Khupse, Nageshwar D.; Kurolikar, Shabana R.; Kumar, Anil (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2010)
This work presents experimental investigations of viscosities of the mixtures of ionic liquids, viz., [bmim][BF(4)] + [bmim][PF(6)] and [hmim][BF(4)] + [hmim][PF(6)] at different temperatures. The temperature dependence of viscosities of these mixtures has been analysed in the light of Vogel-Fulcher-Tammann (VFT) equation with excellent accuracy. The viscosities of the mixtures have been analysed using a simple mixing rule.
Keywords: ionic liquids; viscosity